Cisplatin-induced Ototoxicity Is Mediated by Nitroxidative Modification of Cochlear Proteins Characterized by Nitration of Lmo4 - Jamesdaniel, Samson (American Society for Biochemistry and Molecular Biology, 2012)
Tyrosine nitration is an important sequel of cellular signaling induced by reactive oxygen species. Cisplatin is an anti-neoplastic agent that damages the inner ear through reactive oxygen species and by the formation of DNA adducts. This study reveals a correlation between cisplatin-mediated hearing loss and nitroxidative modification of cochlear proteins and is the first to report nitration of Lmo4. Cisplatin induced a dose-dependent increase in hearing loss in Wistar rats. A 10-15-dB decrease in distortion product amplitude and massive loss of outer hair cells at the basal turn of the cochlea was observed 3 days post-treatment after a 16 mg/kg dose. Cisplatin induced nitration of cellular proteins within the organ of Corti, spiral ganglion, and stria vascularis, which are known targets of cisplatin ototoxicity. Nitration of a 76-kDa cochlear protein correlated with cisplatin dose. The nitrated protein was identified as Lmo4 (LIM domain only 4) by MALDI-TOF (matrix-assisted laser desorption/ionization time of flight) mass spectrometry and confirmed by reciprocal immunoprecipitation and immunoblotting. Co-localization of nitrotyrosine and Lmo4 was particularly high in outer hair cell nuclei after cisplatin treatment. Cochlear levels of Lmo4 were decreased in rats treated with cisplatin. In vitro studies supported the repression of Lmo4 in nitroxidative conditions and the induction of apoptosis upon repression of Lmo4. Inhibition of cochlear protein nitration prevented cisplatin-induced hearing loss. As Lmo4 is a transcriptional regulator that controls the choice between cell survival and cell death, these results support the hypothesis that nitration of Lmo4 influences cisplatin-induced ototoxicity.